SUHU PERMUKAAN LAUT DAN KEDALAMAN TERTANGKAPNYA TUNA OLEH KAPAL PANCING ULUR YANG DILENGKAPI LAMPU - Rama Agus Mulyadi; Muhammad Fedi Alfiadi Sondita; Roza Yusfiandayani (Fakultas Perikanan dan Ilmu Kelautan, 2017)
The movements and abundance of tuna are strongly influenced by the temperature and water depth. Bungus-based fishermen catch bigeye tuna (BET, Thunnus obesus) and yellowfin tuna (YFT, Thunnus albacares) using handlines operated on light-equipped fishing boats. Purpose of the research : (1) to measure the sea surface temperature (SST) and swimming layer bigeye tuna (BET) and yellowfin tuna (YFT) around Mentawai Island, (2) to identification the effect of light on the vertical distribution, and (3) to determine length of hookline the best catch tuna. Based on the length of the line and configuration of line, weight, hooks and live-squid baits, their hooks were at 45, 53, 60, and 68 meters below sea surface. A total of 8 YFT were caught at 45, 53 and 60 m depths; their total weight was 354 kg. One BET of 45 kg was caught at 60 m depth. This study confirmes that these large-sized tunas were caught at a swimming layer of 15-60 m depth. The sea surface temperature (SST) in the fishing ground around Mentawai Island was 28.9 oC in average where fishermen successfuly caught a total of 15 tunas consisting of 3 BETs and 12 YFT. Adult tuna were caught mostly at 23-60 m depth while the juveniles were caught at 15-45 m. This research indicated an effect of light on increasing the position of adult tuna swimming layer. Handline with line of 53 m is the best gear for catching adult tuna in the area.